Presentations of Cutaneous Disease in Various Skin Pigmentations: Hidradenitis Suppurativa - Jamie Y Choe; Henry Lim; Marshall Hall; Christian Scheufele; Dustin V Wilkes; Michael Carletti; Stephen E Weis (HCA Healthcare Journal of Medicine, 2026)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin disorder characterized by recurrent deep-seated nodules and painful abscesses with scars, fistulae, and sinus tracts that predominately affect the intertriginous sites. Onset typically occurs soon after puberty. Depending on disease severity, HS can lead to varying levels of pain, disability, and disfiguration with significant impacts on quality of life. Hidradenitis suppurativa is diagnosed clinically, and no diagnostic tests are specific to the disease. Therefore, clinicians must have the knowledge and competence to identify the clinical features of HS accurately. The purpose of this report is to provide descriptions of characteristic clinical presentations of HS across the full spectrum of skin tones. Although the diagnosis of HS can be challenging, empowering primary care clinicians to identify the key features of this disorder will decrease delays in diagnosis and expedite the initiation of appropriate management in afflicted patients.